2022
DOI: 10.3390/agronomy12020401
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Antioxidant Responses of Lettuce (Lactuca sativa L.) to Arbuscular Mycorrhiza Inoculation and Seaweed Extract Foliar Application

Abstract: Biofertilizers, such as arbuscular mycorrhiza fungi (AMF) and seaweed extract (SWE), have been effective in environmental and agricultural ecosystems. In this study, the effects of AMF, SWE, and their co-application were assayed on the growth and antioxidant potential of lettuce plants. The experiment was conducted as a factorial based on a completely randomized design with two factors and four replications under greenhouse conditions. The first factor was AMF (Glomus mosseae) at two levels consisting of AMF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 66 publications
1
18
1
Order By: Relevance
“…The current investigation demonstrated a synergistic effect of used biostimulants and reported the maximum herb and EO yields were observed when the crop was treated with the congregate application of all three biostimulants ( Figures 6A, B ). These findings are in congruence with some posterior studies demonstrating a synergistic/additive effect of the combined application of a diverse array of biostimulants for augmenting plant growth, production, and even biochemical composition in crops like lettuce ( Rouphael et al., 2017 ; Rasouli et al., 2022 ), green amaranth ( Ngoroyemoto et al., 2020 ), onion ( Gupta et al., 2021a ), and wheat ( Najafi Vafa et al., 2022 ). Moreover, the observed beneficial effects of the combinatory use of biostimulants in the current study might be attributable to the increased photosynthetic pigments, physiological performance, and enhanced N and P contents in the leaves of O. basilicum ( Figures 3A–C ).…”
Section: Discussionsupporting
confidence: 89%
“…The current investigation demonstrated a synergistic effect of used biostimulants and reported the maximum herb and EO yields were observed when the crop was treated with the congregate application of all three biostimulants ( Figures 6A, B ). These findings are in congruence with some posterior studies demonstrating a synergistic/additive effect of the combined application of a diverse array of biostimulants for augmenting plant growth, production, and even biochemical composition in crops like lettuce ( Rouphael et al., 2017 ; Rasouli et al., 2022 ), green amaranth ( Ngoroyemoto et al., 2020 ), onion ( Gupta et al., 2021a ), and wheat ( Najafi Vafa et al., 2022 ). Moreover, the observed beneficial effects of the combinatory use of biostimulants in the current study might be attributable to the increased photosynthetic pigments, physiological performance, and enhanced N and P contents in the leaves of O. basilicum ( Figures 3A–C ).…”
Section: Discussionsupporting
confidence: 89%
“…Also, the increase in TCC might be attributed to the higher availability of macro and micro elements (K, N, Mg, Ca, Zn, and Ni) and better growth of roots by foliar spraying the seaweed extract [ 37 ]. Rasouli et al [ 38 ] reported that the application of seaweed extract increased the photosynthesis rate and chlorophyll index in lettuce plants and, subsequently, caused the accumulation of carbohydrates. On the other hand, our results showed that the application of Si significantly increased the amount of TCC than the control.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of soluble phenols and antioxidant capacity in plants inoculated with mycorrhizae has been reported in French tamarisk (Tamarix gallica) [55], globe artichoke (Cynara cardunculus L. cv. scolymus Fiori) [56], prickly pear cactus (Opuntia ficus-indica) [57], and lettuce (Lactuca sativa L.) [58]. Bencherif et al [55] in T. gallica found that when using a consortium (Funnneliformis mosseae, Septoglomus constrictum, Gigaspora gigantea, Glomus sp1., and Glomus sp2.)…”
Section: Soluble Phenols and Antioxidant Capacitymentioning
confidence: 99%